The form and distribution of microplastic in sediment and water columns of Manado Bay, North Sulawesi - Imanuel, Tonny; Pelle, Wilmy E.; Schaduw, Joshian N. W.; Paulus, James J. H.; Rumampuk, Natalie D. C.; Sangari, Joudy R. R. (Sam Ratulangi University, 2022)
Microplastics are particles measuring <5mm that is the result of degradation from plastic waste that enters the environment. Plastic waste is degraded into microplastics through physical, chemical, and biological processes. Pollutants such as microplastics that enter the waters of Manado Bay can reduce the biological and ecological functions of the ecosystem in the waters. The purpose of this study was to determine the shape and density of microplastics in Manado Bay. The sediment sampling method was carried out by purposive sampling method and for the water, column using a plankton net withdrawal method of 10 meters with 3 replications at 3 stations. The sample will be prepared and then identified. Then the sample density was calculated and then analyzed using a one-way ANOVA test and Pearson correlation. The results showed that there were 4 forms of microplastic found, namely the form of fragments, films, fibers, and foams. The density of sediment sample 1 found 187 microplastic particles with a density of 63.38 particles/kg, at station 2 a total of 479 particles with a density of 182.12 particles/kg, and at station 3 a total of 311 particles with a density of 115.07 particles/kg. In station 1 seawater samples were found 154 particles with a density of 7.26 particles/m³, station 2 a total of 299 particles with a density of 14.10 particles/m³.Keywords: microplastic, shape, density, Manado Bay AbstrakMikroplastik adalah partikel berukuran <5mm hasil degradasi dari sampah plastik yang masuk ke lingkungan. Sampah plastik terdegradasi menjadi mikroplastik melalui proses fisik, kimia, dan biologis. Bahan pencemar mikroplastik yang masuk ke perairan Teluk Manado dapat mengurangi fungsi biologis dan ekologis dari ekosistem yang ada di dalam perairan. Tujuan penelitian ini yaitu untuk mengetahui bentuk dan distribusi mikroplastik yang ada di Teluk Manado. Metode pengambilan sampel sedimen dilakukan dengan metode purposive sampling dan untuk kolom perairan menggunakan metode penarikan plankton net sepanjang 10 meter sebanyak 3 kali ulangan di 3 stasiun. Sampel akan dipreparasi kemudian diidentifikasi. Selanjutnya sampel dihitung kepadatannya kemudian dianalisis menggunakan uji one-way ANOVA dan korelasi Pearson. Hasil penelitian menunjukan bahwa terdapat 4 bentuk mikroplastik yang ditemukan yaitu bentuk fragmen, film, fiber, dan busa. Kepadatan pada sampel sedimen 1 ditemukan 187 partikel mikroplastik dengan kepadatan 63,38 partikel/kg, pada stasiun 2 total 479 partikel dengan kepadatan 182,12 partikel/kg, dan pada stasiun 3 total 311 partikel dengan kepadatan 115,07 partikel/kg. Pada sampel air laut stasiun 1 ditemukan 154 partikel dengan kepadatan 7,26 partikel/m³, stasiun 2 total 299 partikel dengan kepadatan 14,10 partikel/m³.Kata kunci: mikroplastik, bentuk, kepadatan, Teluk Manado